High-content drug screening in zebrafish xenografts reveals high efficacy of dual MCL-1/BCL-XL inhibition against Ewing sarcoma. (1st February 2023) - Grissenberger, Sarah; Sturtzel, Caterina; Wenninger-Weinzierl, Andrea; Radic-Sarikas, Branka; Scheuringer, Eva; Bierbaumer, Lisa; Etienne, Vesnie; Némati, Fariba; Pascoal, Susana; Tötzl, Marcus; Tomazou, Eleni M.; Metzelder, Martin; et al.
Abstract: Ewing sarcoma is a pediatric bone and soft tissue cancer with an urgent need for new therapies to improve disease outcome. To identify effective drugs, phenotypic drug screening has proven to be a powerful method, but achievable throughput in mouse xenografts, the preclinical Ewing sarcoma standard model, is limited. Here, we explored the use of xenografts in zebrafish for high-throughput drug screening to discover new combination therapies for Ewing sarcoma. We subjected xenografts in zebrafish larvae to high-content imaging and subsequent automated tumor size analysis to screen single agents and compound combinations. We identified three drug combinations effective against Ewing sarcoma cells: Irinotecan combined with either an MCL-1 or an BCL-XL inhibitor and in particular dual inhibition of the anti-apoptotic proteins MCL-1 and BCL-XL, which efficiently eradicated tumor cells in zebrafish xenografts. We confirmed enhanced efficacy of dual MCL-1/BCL-XL inhibition compared to single agents in a mouse PDX model. In conclusion, high-content screening of small compounds on Ewing sarcoma zebrafish xenografts identified dual MCL-1/BCL-XL targeting as a specific vulnerability and promising therapeutic strategy for Ewing sarcoma, which warrants further investigation towards clinical application. Highlights: High-content drug screening in zebrafish xenografts discovers compound combinations effective against Ewing sarcoma. Combining topoisomerase I inhibitors with anti-apoptotic protein inhibitors enhances single agent efficacy. Ewing sarcoma cells are highly sensitive to dual targeting of anti-apoptotic proteins MCL-1 and BCL-XL . MCL-1 and BCL-XL represent therapeutic targets across Ewing sarcomas.